Determinasi Kinerja Karyawan Ditinjau dari Kompensasi dan Pelatihan di PT Cita Indonesia Bersih - Tedi Apriansyah; Widhi Ariyo Bimo; Hendri Maulana (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2026)
This study aims to analyze the effect of compensation and training on employee performance at PT Cita Indonesia Bersih. The population in this study consists of employees known as rangers within the company. The research method employed is a quantitative approach with descriptive and verificative designs. Data were collected through the distribution of questionnaires to all respondents, totaling 60 individuals, using a saturated sampling (census) technique, in which the entire population is used as the research sample. The data were analyzed using Structural Equation Modeling based on Partial Least Squares (SEM-PLS). The results of the study indicate that, partially, compensation has a positive and significant effect on employee performance. Training also has a positive and significant effect on employee performance. Simultaneously, compensation and training have a significant effect on employee performance, with a contribution of 83.6%, while the remaining 16.4% is influenced by other variables outside the scope of this study. The conclusion of this study indicates that the better the compensation provided and the more effective the training implemented, the higher the level of employee performance. Therefore, the management of PT Cita Indonesia Bersih is expected to maintain a fair compensation system and enhance the quality of training programs in order to support optimal employee performance.